Association between insulin resistance and left ventricular diastolic dysfunction in non-diabetic general population. (25th November 2020) - Kamon, T; Kaneko, H; Itoh, H; Kiriyama, H; Koyama, K; Fujiu, K; Morita, H; Uno, K; Hayashi, N; Komuro, I
Abstract: Background: Insulin resistance due to visceral fat accumulation plays a central role in the development of diabetic mellitus and subsequent cardiovascular disease. Abdominal obesity and diabetic mellitus are associated with the progression of left ventricular diastolic dysfunction which is the major structural abnormality in patients with heart failure. However, whether insulin resistance influences left ventricular diastolic dysfunction in non-diabetic subjects is unclear. Purpose: In this study, we aimed to clarify the association between insulin resistance and left ventricular diastolic dysfunction in non-diabetic general population. Methods: We examined 2, 572 non-diabetic subjects with preserved left ventricular systolic function (ejection fraction ≥50%) and without a past history of diabetic mellitus, heart failure, coronary artery disease, atrial fibrillation, stroke, moderate to severe valvular disease, who underwent medical check-ups at the University of Tokyo Hospital from January 2009 to December 2018. Diabetes mellitus was defined as fasting glucose level ≥126 mg/dL or a subject's use of oral antidiabetic medications or insulin. We calculated the Homeostasis Model Assessment-Insulin Resistance (HOMA-IR) score [HOMA-IR = fasting glucose (mg/dL) × insulin (μU/mL) / 405], and defined insulin resistance as HOMA-IR ≥2.5. Left ventricular diastolic function was assessed by echocardiography, using tissue doppler analysis (E/E' ratio in septal and lateral). Visceral adiposity was assessed as visceral fat volume measured by computed tomography scanner. Results: Mean age was 53.3±9.8 years, and 1, 746 subjects (67.9%) were male. Overall, HOMA-IR was 1.1 on average, and HOMA-IR ≥2.5 was observed in 5.0% of study population. BMI and the prevalence of obesity were higher in subjects with HOMA-IR ≥2.5 than in those without. There was no significant difference in left ventricular ejection fraction between HOMA-IR ≥2.5 and ≤2.5. E/E' ratio in septal and lateral were higher in subjects with HOMA-IR ≥2.5 than in those without. Multivariable logistic regression analysis demonstrated that obesity and waist circumference, visceral fat volume were independently associated with HOMA-IR ≥2.5, however, age, hypertension, hypercholesterolemia were not. Further, multiple regression analysis including insulin resistance, age, male gender, obesity, hypertension, hypercholesterolemia, cigarette smoking and visceral fat volume, showed that insulin resistance was an independent determinant of increasing E/E' in both septal and lateral, whereas visceral fat volume was not (Figure 1). Conclusion: The results of the present study suggest that insulin resistance due to visceral fat accumulation might be associated with the development of left ventricular diastolic dysfunction in non-diabetic general population without overt cardiovascular disease. Funding Acknowledgement: Type of funding source: None